Water–fat Dixon sequences in the evaluation of breast implants: proposal of a time effective rapid approach in the clinical practice. Issue 9 (September 2017) - Marcon, M.; Becker, A.S.; Ulbrich, E.J.; Frauenfelder, T.; Boss, A.
Abstract : Aim: To evaluate the diagnostic accuracy achieved from a fat–water Dixon sequence alone compared to a combination of a silicone-specific magnetic resonance imaging (MRI) sequence and a water-specific MRI sequence in the assessment of breast implants. Materials and methods: In this institutional review board (IRB)-approved study the integrity of breast implants was assessed retrospectively in 27 patients undergoing breast MRI at 3 T. A qualitative evaluation of (set 1) a silicon-selective water-saturated short tau inversion recovery (STIR) sequence in combination with a water-only Dixon dataset (total acquisition time 7 minutes 17 seconds), and of (set 2) fat-only and water-only Dixon datasets (4 minutes 8 seconds) was performed by two readers independently evaluating the following features: margin definition of the implant, water suppression homogeneity, image quality, presence of artefacts and their effects on the imaging interpretation, and diagnostic confidence. Diagnostic accuracy in implant rupture detection was determined and either surgical confirmation or diagnosis from the radiological report was used as a standard of reference. Results: In both sequences, margin definition of the implant wall, water suppression homogeneity, and overall image quality were rated good–excellent in most of cases. Water suppression homogeneity was moderate–poor in a greater number of cases in set 1. Movement artefacts were more frequent in set 1 whereas five cases (18.5%) exhibited swap artefacts between silicone and water in set 2. Diagnostic confidence was rated high–very high with both sequences in most of cases. Diagnostic accuracy was 100% for both readers using set 1 and 96.2% and 100% using set 2. Conclusion: A single Dixon sequence allows an accurate diagnostic evaluation of breast implants and concomitant shortening of the overall acquisition time. Highlights: Fat-/water-Dixon sequences can be used alone for the evaluation of implants rupture. Diagnostic accuracy is similar to that achieved by using silicone-specific imaging. A shortening of the overall scan time can be obtained.